Poly(styrene)/oligo(fluorene)-intercalated fluoromica hybrids: synthesis, characterization and self-assembly - Leone, Giuseppe; Galeotti, Francesco; Porzio, William; Scavia, Guido; Barba, Luisa; Arrighetti, Gianmichele; Ricci, Giovanni; Botta, Chiara; Giovanella, Umberto (Beilstein Journal of Nanotechnology, 2014)
We report on the intercalation of a cationic fluorescent oligo(fluorene) in between the 2D interlayer region of a fluoromica type silicate. The formation of intercalated structures with different fluorophore contents is observed in powders by synchrotron radiation XRD. Successively, the hybrids are dispersed in poly(styrene) through in situ polymerization. Such a procedure allows us to synthesize the materials from solution, to achieve solid films, and to characterize them by optical and morphologic techniques. The polymeric films with homogeneous distribution of the hybrids exhibit ultraviolet–blue photoluminescence with a significantly enhanced photostability compared to the bare oligo(fluorene)s. Finally, under specific conditions, the polymer hybrid with higher oligo(fluorene) content spontaneously assembles into highly ordered microporous films.
Keywords: breath figures; fluoromica; layered silicates; oligo(fluorene); photostability; self-assembly